Creative commons: A convergence model between the ideal of commons and the possibilities of creation in contemporary times, opposed to copyright impediments - Mass Araya, Elizabeth Roxana [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (SAGE Publications, 2012)
The contemporary individual finds on the Internet and especially on the Web facilitating conditions to build a basic infrastructure based on the concept of commons. He also finds favorable conditions which allow him to collaborate and share resources for the creation, use, reuse, access and dissemination of information. However, he also faces obstacles such as Copyright (Law 9610/98 in Brazil). An alternative is Creative Commons which not only allows the elaboration, use and dissemination of information under legal conditions but also function as a facilitator for the development of informational commons. This paper deals with this scenario.
Keywords: Commons; Copyright; Creative commons; Information and technology; Information science; Web 2.0; Convergence model; Creative Commons; Facilitating conditions; Favorable conditions; Copyrights; Electronic publishing; World Wide Web